Horizons of nanotechnology applications in female specific cancers. (February 2021) - Rajitha, Balney; Malla, Rama Rao; Vadde, Ramakrishna; Kasa, Prameswari; Prasad, Ganji Lakshmi Vara; Farran, Batoul; Kumari, Seema; Pavitra, Eluri; Kamal, Mohammad Amjad; Raju, Ganji Seeta Rama; Peela, Sujatha; Nagaraju, Ganji Purnachandra
Highlights: Female specific cancers are a major health burden affecting women. Early detection methods and treatment strategies for these cancers are limited. Nanotechnology-based diagnostic tools can improve detection and diagnosis of female cancers. Nanotechnology-based therapeutic strategies can enhance drug delivery and cytotoxicity in female-specific cancers. Abstract: Female-specific cancers are the most common cancers in women worldwide. Early detection methods remain unavailable for most of these cancers, signifying that most of them are diagnosed at later stages. Furthermore, current treatment options for most female-specific cancers are surgery, radiation and chemotherapy. Although important milestones in molecularly targeted approaches have been achieved lately, current therapeutic strategies for female-specific cancers remain limited, ineffective and plagued by the emergence of chemoresistance, which aggravates prognosis. Recently, the application of nanotechnology to the medical field has allowed the development of novel nano-based approaches for the management and treatment of cancers, including female-specific cancers. These approaches promise to improve patient survival rates by reducing side effects, enabling selective delivery of drugs to tumor tissues and enhancing the uptake of therapeutic compounds, thus increasing anti-tumor activity. In this review, we focus on the application of nano-based technologies to the design of novel and innovative diagnostic and therapeutic strategies in the context of female-specific cancers, highlighting their potential uses and limitations.